2020
DOI: 10.1139/cjb-2019-0192
|View full text |Cite
|
Sign up to set email alerts
|

Application of the hydrotime model to assess seed priming effects on the germination of rapeseed (Brassica napus L.) in response to water stress

Abstract: Our aim was to determine whether the parameters of the hydrotime model can be used to compare the effects of seed priming treatments on germination. Seeds of three rapeseed cultivars (‘H61’, ‘H4815’, and ‘DK003’) were exposed to priming treatments and then their germination was tested at different water potentials. Seed priming improved the germination percentage, which was higher in ‘H4815’ than in the other two cultivars, and it increased germination rate (decreased θH) and uniformity (decreased σψb). The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…However, while it is individual seeds that face the dilemma of whether to germinate now or wait until later, it is the collective action of populations of seeds that ultimately determines the success of the species or crop, whether in nature or in agricultural fields (Mitchell et al, 2017;Gremer et al, 2020). In nature, species whose seeds can more accurately predict the optimal time to germinate in their environment have a greater probability of long-term success in that environment (Larson and Funk, 2016;ten Brink et al, 2020). There are still risks involved, however, due to variability in environmental conditions, leading to bet-hedging strategies in which the seed population as a whole consists of subpopulations responding differently in variable environments (Gremer et al, 2016;Gianella et al, 2021).…”
Section: Basis Of Population-based Approaches To Seed Biologymentioning
confidence: 99%
See 2 more Smart Citations
“…However, while it is individual seeds that face the dilemma of whether to germinate now or wait until later, it is the collective action of populations of seeds that ultimately determines the success of the species or crop, whether in nature or in agricultural fields (Mitchell et al, 2017;Gremer et al, 2020). In nature, species whose seeds can more accurately predict the optimal time to germinate in their environment have a greater probability of long-term success in that environment (Larson and Funk, 2016;ten Brink et al, 2020). There are still risks involved, however, due to variability in environmental conditions, leading to bet-hedging strategies in which the seed population as a whole consists of subpopulations responding differently in variable environments (Gremer et al, 2016;Gianella et al, 2021).…”
Section: Basis Of Population-based Approaches To Seed Biologymentioning
confidence: 99%
“…The germination kinetics of primed seeds can also be characterized by HTT models Bradford and Somasco, 1994;Cheng and Bradford, 1999;Patanè et al, 2016;Tatari et al, 2020). The improvements in germination rates and uniformity are primarily due to smaller values for θ HT rather than to the lowering of ψ b (50).…”
Section: Priming and Seed Enhancement (Hydrothermal Priming Time Model)mentioning
confidence: 99%
See 1 more Smart Citation
“…Some substances are used to simulate water stress conditions in germination under controlled conditions, such as mannitol and polyethylene glycol (PEG 6000). During conditioning, the seeds absorb water in quantities necessary to activate the germination metabolism, however, the imbibition of the seed is stopped before the protrusion of the radicle [6].…”
Section: Highlightsmentioning
confidence: 99%
“…In particular, previous studies have reported the close relationship between hydrotime model parameters and seedling emergence, and thus seed vigor, in many plant species, including alfalfa [39], cotton (Gossypium hirsutum L.) [40], rapeseed (Brassica napus L.) [41], and sugar beet (Beat vulgaris L.) [42]. It has also been reported that seed priming can increase the germination speed under water stress conditions by reducing θ H or Ψ b(g) [43][44][45][46], which implies that the change in hydrotime model parameters resulting from seed priming may be closely associated with seed vigor and the performance of seeds/seedlings in unfavorable field environments. However, to our knowledge, little literature is available concerning the description of CMV seed germination in response to water potential based on the hydrotime model, and the hypothesis that hydrotime model parameters can be applied to estimate seed vigor and predict the seedling emergence performance of forage legumes, including CMV, has not been validated.…”
Section: Introductionmentioning
confidence: 99%